Biochemical Characterization of Some Varieties of Apricot Present in the Vesuvius Area, Southern Italy - Fratianni, Florinda; Cozzolino, Rosaria; d'Acierno, Antonio; Ombra, Maria Neve; Spigno, Patrizia; Riccardi, Riccardo; Malorni, Livia; Stocchero, Matteo; Nazzaro, Filomena (Frontiers in Nutrition, 2022)
The witnesses of the millenary history of the so-called “Campania felix”, in the South of Italy, highlighted that several fruit and vegetables cultivated on such territory could potentially be a treasure trove of healthfully important elements. Our work evaluated the content of β-carotene, ascorbic acid, total phenolics, and antioxidant activity of ten typical varieties of apricots cultivated in the Vesuvius area, in the Campania region. The analysis of correlation performed taking into account such parameters evidenced that the antioxidant activity was influenced mainly by the content of total polyphenols and slightly less by the content of ascorbic acid, never by -carotene. The dendrogram clustered eight varieties in two main groups; on the other hand, two varieties (“Vitillo,” and “Preveta bella”) seemed hierarchically distant. The Gas Chromatography-Mass Spectrometry analysis of Volatile Organic Compounds (VOCs), herein performed for the first time, evidenced the influence of the varieties on the VOCs profiles, both from a qualitative and semi-quantitative point of view, discriminating the varieties in different clusters, each of them characterized by specific notes.